Leakage Investigation on a Fired Heater Tube of a Petroleum Refinery due to Carburization - D.N. Adnyana (Metalurgi, 2019)
The fired heater of a petroleum processing refinery leaks in one of the convection tubes. The tube is made of ASTM A-106 Gr.B. Process fluid in the tube is xylene with a design pressure of 15.8 kg/cm²g and design temperature of 299 °C (at the inlet) and 405 °C (at the outlet). This study aims to determine the type and causes and the mechanism of leakage in the tube. A number of tests have been carried out including visual inspection and  macroscopic analysis, chemical analysis, metallographic and hardness testing, and SEM (scanning electron microscopy) analysis which is equipped with EDS (energy dispersive spectroscopy). The results obtained showed that the leak that occurred in the convection tube was caused by carburization and metal dusting. Carburization occurs in the inner walls of the tube that experience some localized overheating due to the formation of coke deposits. AbstrakDapur pemanas pada sebuah kilang pengolahan minyak bumi mengalami kebocoran pada salah satu pipa konveksi. Pipa tersebut terbuat dari baja karbon rendah jenis ASTM A-106 Gr.B. Cairan proses di dalam pipa adalah xylene dengan tekanan desain 15,8 kg/cm²g dan suhu desain yaitu 299 °C (pada saluran masuk) dan 405 °C (pada saluran keluar). Penelitian ini bertujuan untuk menentukan jenis dan faktor penyebab serta mekanisme terjadi kebocoran pada pipa tersebut. Sejumlah pengujian telah dilakukan meliputi pemeriksaan visual dan makroskopik, analisa kimia, pengujian metalografi dan kekerasan, serta analisa SEM (scanning electron microscopy) yang dilengkapi dengan EDS (energy dispersive spectroscopy). Hasil penelitian yang diperoleh menunjukkan bahwa kebocoran yang terjadi pada pipa konveksi disebabkan oleh karburisasi dan pembentukan debu/serbuk logam. Karburisasi terjadi pada dinding bagian dalam pipa yang mengalami panas berlebih secara lokal akibat terbentuknya endapan kokas.